Nutritional care in motor neurone disease/ amyotrophic lateral sclerosis - Cristina Cleide dos Santos Salvioni; Patricia Stanich; Claudinéa S. Almeida; Acary Souza Bulle Oliveira (Arquivos de Neuro-Psiquiatria)
Patients with amyotrophic lateral sclerosis (ALS) often present changes in nutritional status. Based on weight loss and on difficulty in nutritional management, this study aims to review the different possibilities and to present guidelines concerning nutritional treatment to such patients. Diet characteristics, types of treatment and nutritional therapy indicating administration routes and discussing the details of the disease are described herein. Nutritional therapy has been a substantial therapeutic resource for ALS development.